Tribological properties of titanium alloys under lubrication of SEE oil and aqueous solutions. (May 2017) - Yang, Ye; Zhang, Chenhui; Dai, Yuanjing; Luo, Jianbin
Abstract: The tribological behaviors of titanium alloy–tungsten carbide friction pair lubricated by oil or water based lubricants are investigated with the help of universal tribotester. The results show that self-emulsifying ester (SEE), either oil phase or aqueous solution, has good friction reduction performance on titanium alloys while the commonly used paraffin and PAO fail to lubricate this system. Furthermore, it demonstrates that SEE aqueous solution with 1 wt% concentration presents a better anti-wear property than the oil phase. It can decrease the adhesive and abrasive wear greatly. The surfaces inside and outside wear track are detected by ToF-SIMS. The high polarity of the molecules and good thermal conductivity of the aqueous solution lead to the excellent lubricating and anti-wear properties for titanium alloys. Highlights: The tribological behaviors of titanium alloys lubricated by oil or water based lubricants are investigated. SEE oil phase and aqueous solution showed excellent lubricating property for titanium alloys. The aqueous solution could decrease adhesive wear even better than the oil phase and had better load capacity. The lubricating mechanism of SEE was further investigated. SEE is a candidate additive in developing cutting fluid of titanium alloys.